New technology in libraries work and the problems of education in the field of librarianship and bibliography - Marija Prokopčik (Knygotyra)
The article deals with the problem of the changing demands of education for librarianship and information work in developed capitalist countries as a result of the application of computers and changing technology of library work. There are indications that, under these conditions, education and training must be something rather different from traditional library education.